1997
DOI: 10.1021/ef960138w
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature NOx Removal for Flue Gas Cleanup

Abstract: NO x reduction with hydrocarbons is studied at temperatures around 150 °C to develop an easy retrofit NO x removal process to be located downstream of the particulate control device for flue gas cleanup. Acetone is the most active hydrocarbon reductant for NO reduction in the presence of O2 and H2O. At 150 °C, 35% NO reduction was obtained over 5% Cu−2% Ag/PCB. The activity, however, is greatly decreased by the presence of SO2. NO oxidation to NO2 is studied for further improving the NO reduction activity be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Supported gold nanoparticles can catalyze a wide variety of reactions including the reduction of NO x by hydrocarbons [35,36], the oxidation CH 4 [37,38], CO [39], and propene [40], and the epoxidation of propylene [41]. Gold is extensively used as a substrate for selfassembled monolayers (SAM) [42,43] in materials science [44], as interconnects in electronic devices [45][46][47], as a substrate for conducting polymers in chemical sensors [48], and in many different types of biosensors [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Supported gold nanoparticles can catalyze a wide variety of reactions including the reduction of NO x by hydrocarbons [35,36], the oxidation CH 4 [37,38], CO [39], and propene [40], and the epoxidation of propylene [41]. Gold is extensively used as a substrate for selfassembled monolayers (SAM) [42,43] in materials science [44], as interconnects in electronic devices [45][46][47], as a substrate for conducting polymers in chemical sensors [48], and in many different types of biosensors [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…A method was also described for preparing GNPs supported on CoO x which exhibited high resistance to SO 2 and H 2 O and high catalytic activity for the selective oxidation of NO at a relatively low temperature of 120°C [90]. Interestingly, it was found that SO 2 enhanced the catalytic activity of Au/CoO x in the oxidation of NO [91]. However, development of catalysts with high sulphur resistance remains a challenge.…”
Section: Future Directions and Challengesmentioning
confidence: 99%
“…Thus, developing active SCR catalysts that can be used at relatively low temperatures (for example below 250 • C) is needed, so that SCR systems could be installed downstream of the desulfurizer and electrostatic precipitator. Low-temperature catalysts contribute to lower energy consumption and help simplify the retrofitting of SCR devices for flue gas cleaning [12].…”
Section: Introductionmentioning
confidence: 99%